Understanding adaptive regulation of skeletal muscle physiology in the Weddell seal: a proteomics approach - Cable, Amber E. (Amber Elizabeth), author; Kanatous, Shane, advisor; Florant, Gregory L., committee member; Mykles, Donald L., committee member; Bell, Christopher, committee member (Colorado State University. Libraries, 2010)
Air-breathing, diving vertebrates foster unique adaptations to exercise; namely, these animals are able to exercise for prolonged periods of time while "holding" their breath. Weddell seals (Leptonychotes weddellii) routinely undergo progressive hypoxia and ischemia throughout the course of diving activity. In essence, this unique animal has overcome problems that are considered to be otherwise pathological in terrestrial vertebrates. The goal of this project was to verify the use of cross-species analysis and develop a proteomics protocol for use in diving mammals. These steps are necessary in order to ultimately use proteomics to identify age class protein signatures and better understand the molecular regulation of the physiological changes that couple the development of inactive Weddell seal pups into elite diving adults. Proteins from the primary swimming muscle (M. longissimus dorsi) of two distinct age classes, pups (3-5 weeks/nondivers) and adults (7+ years/expert divers), were visualized using two dimensional gel electrophoresis (2DE), quantified, and identified. This study validated the use of cross-species analysis, which was of paramount importance due to the fact that the pinniped genome is largely unidentified, and established a 2DE protocol tailored to suit the unique properties of diving mammal skeletal muscle tissue. To our knowledge, this was the first study in which proteomics was applied to study the proteome of a diving mammal. Understanding the control of these adaptations in the Weddell seal, which develops its ability to endure hypoxia associated with breath-hold exercise rather than being born ready to dive, has considerable potential for pharmacological implications for treating various human diseases, specifically those that involve hypoxic conditions such as cardiovascular and pulmonary diseases.
Department Head: Daniel R. Bush.